Breast cancer services in Vietnam: a scoping review. Issue 1 (1st January 2018) - Jenkins, Chris; Minh, Luu Ngoc; Anh, Tran Tuan; Ngan, Tran Thu; Tuan, Ngo Tri; Giang, Kim Bao; Hoat, Luu Ngoc; Lohfeld, Lynne; Donnelly, Michael; Van Minh, Hoang; Murray, Liam
ABSTRACT: Background : Breast cancer incidence has been increasing consistently in Vietnam. Thus far, there have been no analytical reviews of research produced within this area. Objectives : We sought to analyse the nature andextent of empirical studies about breast cancer in Vietnam, identifying areas for future research and systemsstrengthening. Methods : We undertook a scoping study using a five-stage framework to review published and grey literature in English and Vietnamese on breast cancer detection, diagnosis and treatment. We focused specifically on research discussing the health system and service provision. Results : Our results show that breast cancer screening is limited, with no permanent or integrated national screening activities. There is a lack of information on screening processes and on the integration of screening services with other areas of the health system. Treatment is largely centralised, and across all services there is a lack of evaluation and data collection that would be informative for recommendations seeking to improve accessibility and quality of breast cancer services. Conclusions : This paper is the first scoping review of breast cancer services in Vietnam. It outlines areas for future focus for policy makers and researchers with the objective of strengthening service provision to women with breast cancer across the country while also providing a methodological example for how to conduct a collaborative scoping review.